2002
DOI: 10.1038/sj.ejhg.5200806
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Paraoxonase (PON1) locus reveals an increased frequency of Arg192 allele in centenarians

Abstract: Human Paraoxonase (PON1) is a High-Density Lipoprotein (HDL)-associated esterase that hydrolyses lipo-peroxides. PON1 has recently attracted attention as a protective factor against oxidative modification of LDL and may therefore play an important role in the prevention of the atherosclerotic process. Two polymorphisms have been extensively studied: a Leucine (L allele) to Methionine (M allele) substitution at codon 55, and a Glutamine (A allele) to Arginine (B allele) substitution at codon 192. We have examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 27 publications
4
38
0
3
Order By: Relevance
“…9 Few studies, however, have investigated the impact of PON1 polymorphisms on survival. Heijmans et al 10 found no significant effect of the Q192R and M55L polymorphisms on mortality risk in 666 subjects age 85 þ years in a 10-year follow-up study, whereas Bonafé et al 11 reported an increase in the frequency of 55M/192R carriers in 308 centenarians as compared to 579 younger individuals. In this study, we examined the association between the À107C/T, M55L and Q192R polymorphisms in a sample of Danish subjects aged 47 -93 years drawn among participants of three populations-based studies.…”
Section: Introductionmentioning
confidence: 99%
“…9 Few studies, however, have investigated the impact of PON1 polymorphisms on survival. Heijmans et al 10 found no significant effect of the Q192R and M55L polymorphisms on mortality risk in 666 subjects age 85 þ years in a 10-year follow-up study, whereas Bonafé et al 11 reported an increase in the frequency of 55M/192R carriers in 308 centenarians as compared to 579 younger individuals. In this study, we examined the association between the À107C/T, M55L and Q192R polymorphisms in a sample of Danish subjects aged 47 -93 years drawn among participants of three populations-based studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent association studies are increasingly emphasizing the important roles that genes may play in affecting human survival at advanced ages (Bonafe et al 2002;Christiansen et al 2004;Bellizzi et al 2005;Hurme et al 2005). Further studies using efficient analytical tools are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PON1 gene polymorphisms have been found to affect human survival (Bonafe et al 2002;Christiansen et al 2004). In the study by Christiansen et al (2004), three SNPs in the PON1 gene (two in the coding region, amino acids M55L and Q192R, and one in the promoter region, C-107T) were genotyped.…”
Section: Example Applicationmentioning
confidence: 99%
“…Genetic analysis of human ageing is mainly approached by searching the genetic basis of susceptibility to major geriatric disorders or the allelic contributions to exceptionally long life span. It is just thanks to these last studies in centenarians populations that several candidate longevity genes or pathways including PON1 [19,130], IGF1/insulin pathway [84,120], elements of lipid metabolism [12], stress response [34] and inflammatory response have been identified [53].…”
Section: Human Genes and Longevitymentioning
confidence: 99%
“…Genetic analysis of human ageing is mainly approached by searching the genetic basis of susceptibility to major geriatric disorders or the allelic contributions to exceptionally long life span. It is just thanks to these last studies in centenarians populations that several candidate longevity genes or pathways including PON1 [19,130], IGF1/insulin pathway [84,120], elements of lipid metabolism [12], stress response [34] and inflammatory response have been identified [53].Genes related to inflammation and stress response, in particular the pro-inflammatory cytokines IL-1, IL-6, TNFalpha, the anti-inflammatory cytokine IL-10, the HSP70 chaperones and the regulators of trace elements homeostasis, metallothioneins (MT), seem particularly relevant taking into account that the same genes are involved in the susceptibility to major geriatric disease/disorders such as …”
mentioning
confidence: 99%